Archibald Versus Chicago - Stigler, George J. (Review of Economic Studies, 1963)
Journal Article Archibald versus Chicago Get access George J. Stigler George J. Stigler Chicago Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 1, February 1963, Pages 63–64, https://doi.org/10.2307/2296032 Published: 01 February 1963